2004
DOI: 10.1097/01.ta.0000124462.61495.45
|View full text |Cite
|
Sign up to set email alerts
|

Protocol-Driven Ventilator Weaning Reduces Use of Mechanical Ventilation, Rate of Early Reintubation, and Ventilator-Associated Pneumonia

Abstract: Protocol-driven weaning reduces use of mechanical ventilation and VAP. Injured and general surgical patients show reduction in complications, but shorter ICU LOS depends on resources elsewhere in the health care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(50 citation statements)
references
References 38 publications
1
42
0
6
Order By: Relevance
“…Observational studies from both medical and surgical ICUs have reported that spontaneous breathing trials and targeted/daily sedation interruptions (irrespective of other VAP prevention measures) reduced the prevalence of VAP from ϳ15 to 5%. This corresponded with a decrease in the mean duration of mechanical ventilation to fewer than 5 d. 105,106 In another study, targeted sedation reduced the average duration of mechanical ventilation from 10.3 to 4.4 d with a corresponding trend toward reduced VAP from 20.4 to 8.3% (P ϭ .10). 107 …”
Section: Weaning and Sedation Strategiesmentioning
confidence: 90%
“…Observational studies from both medical and surgical ICUs have reported that spontaneous breathing trials and targeted/daily sedation interruptions (irrespective of other VAP prevention measures) reduced the prevalence of VAP from ϳ15 to 5%. This corresponded with a decrease in the mean duration of mechanical ventilation to fewer than 5 d. 105,106 In another study, targeted sedation reduced the average duration of mechanical ventilation from 10.3 to 4.4 d with a corresponding trend toward reduced VAP from 20.4 to 8.3% (P ϭ .10). 107 …”
Section: Weaning and Sedation Strategiesmentioning
confidence: 90%
“…Os protocolos são desenvolvidos com base em evidências, as quais tendem a ser inseridas em um fluxograma, e são elaborados por especialistas de acordo com as características de cada UTI. Diversos estudos têm demonstrado a superioridade do desmame seguindo protocolos (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Nota-se essa falta de metodologia quando observamos as técnicas utilizadas no GC, no qual se observaram técnicas pouco recomendadas, como o SIMV, além de outros métodos, como a utilização do modo assistido controlado na modalidade ciclada a volume.…”
Section: Discussionunclassified
“…Essa estratégia pode repercutir em desfechos ruins, evidenciando a necessidade de implementar técnicas para identificar os pacientes elegíveis para o desmame e a sua transição para a ventilação espontânea deve seguir estratégias eficazes e comprovadas, favorecendo a utilização dos protocolos (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionunclassified
“…Other studies of RT-protocol-based liberation from mechanical ventilation have shown mixed results, with one observational study supporting benefit 20 and another pseudorandomized study not showing benefit. 21 As the authors noted in the latter study, the level of physician staffing of the ICU was "generous" enough (ie, 2 attending physicians and 10 physicians-in-training staffed a closed 14-bed ICU) to obscure any possible incremental impact of protocols.…”
Section: Are Respiratory Protocols Effectivementioning
confidence: 99%